Eucalyptus and spearmint oils inhibit the biological activity of lesser grain borer and red flour beetles - Ali, Azher M.; Sabit, Falah A. (Journal of Aridland Agriculture, 2023)
The objective of this investigation was to assess the insecticidal efficacy of essential oils derived from eucalyptus (Eucalyptus camaldulensis) and spearmint (Mentha spicata) against two species of stored-product insects. The process of Clevenger-type water distillation was employed to extract essential oils from two distinct plant species. Subsequently, the insecticidal properties of these oils were evaluated against specimens of the American wheat weevil (Rhyzopertha dominica) and the red flour beetle (Tribolium castaneum), belonging to the Coleoptera: Bostrichidae and Tenebrionidae families, respectively. Eucalyptus oil exhibited the highest level of inhibition of insects’ reproduction. Still, when tested on adults of both types of insects, eucalyptus and spearmint oils were more effective than the control treatment. A complete inhibition of egg-laying activity (100%) was achieved using a 7% concentration of eucalyptus oil. The trials were done within controlled laboratory settings, with a notable absence of tests conducted under authentic operational conditions. Researchers who want to learn more about using essential oils as insecticides in the future should focus on making pesticide formulations that work well in a wide range of production settings.